Cancer mortality in Italian populations: differences between Italy and the USA. Issue 4 (26th August 2021) - Santucci, Claudia; Medina, Heidy N.; Carioli, Greta; Negri, Eva; La Vecchia, Carlo; Pinheiro, Paulo S.
Abstract : Background: The comparison of cancer mortality rates and risk factors among foreign-born populations in a host country with those in the country of origin provides insights into differences in access to care, timely diagnosis, and disease management between the two countries. Methods: Using 2008–2018 cancer mortality data for the Italian population and for Italy-born Americans, we calculated age-standardized mortality rates (ASMRs) and standardized mortality ratios (SMRs). Results: ASMRs were lower in Italy-born Americans (201.5 per 100 000) compared to Italians (255.1 per 100 000). For all neoplasms combined, SMRs for Italy-born American men and women were 0.75 [95% confidence interval (CI), 0.73–0.77] and 0.78 (95% CI, 0.76–0.80), respectively. Among men, the SMRs were significantly below 1 for oral cavity, stomach, colorectal, liver, lung, prostate, bladder and kidney cancer. Among women, the SMRs were 0.69 for oral, 0.40 for stomach, 0.61 for colorectal, 0.72 for liver, 0.73 for breast and 0.53 for kidney cancers. Mortality was not reduced for lung (1.02, 95% CI, 0.94–1.10) cancer in women. Conclusion: Generational differences in smoking prevalence patterns between the US and Italy may explain the advantages for Italy-born Americans for lung and other tobacco-related cancers compared to their Italian men counterparts. Lower prevalence of Helicobacter pylori, alcohol consumption, hepatitis B and C virus in the USA may justify the lower mortality for stomach and liver cancer, among Italy-born Americans. Earlier and more widespread adoption of cancer screening and effective treatments in the USA is likely to be influential in breast, colorectal and prostate cancer mortality.